An eco-structuralism approach in soundscape (data) composition - Gomes, J.A.; Barbosa, A.; Penha, R. (ACM International Conference Proceeding Series, 2014)

Editorial: On Cinema - Ribas, Daniel; Crespo, Nuno; Caires, Carlos Sena (Journal of Science and Technology of the Arts, 2020)
In the past decades, the field of cinema has undergone several transformations. The digital turn increasingly called for new forms of production, distribution, and exhibition, which imply different ways of thinking, doing, and experimenting cinema. These new forms also reduced the gap between cinema to other so-called visual arts. If cinema and visual arts were already in the process of merging, the last years forced the naturalization of thinking in similar theoretical grounds. This special issue aims to be a forum for the discussion of new practices of researching cinema, and the changes in cinema’s forms of experience and production.
Keywords: Art and cinema; Cinema; Contemporary cinema; Digital turn; Visual Arts

NIME education at the school of arts of the portuguese catholic university/CITAR - Martins, L.G.; Barbosa, A. (Proceedings - 2013 Learning and Teaching in Computing and Engineering, LaTiCE 2013, 2013)

Static recording apparatus for soundscape analysis in Macau - Estadieu, Gerald; Cheung, Yin Yan; Pestana, Pedro Duarte; Barbosa, Alvaro (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2023)
The concept of Soundscape was initially proposed to study the relationship between humans and their sonic environment. It has gathered momentum from academia to environmentalists and policymakers throughout the years. The study and characterisation of Soundscapes can be complex as it tries to take a holistic and qualitative approach rather than simply quantifying sound pressure levels. This paper introduces a comprehensive Soundscape study process in an ongoing research project in Macao (China), a small territory (32.9 km2) and one of the most densely populated areas in the world. The paper seeks to show a first version of a technical solution to systematically capture the local soundscape, analyse it, classify it, and ultimately deliver a dataset library and the intangible qualities of the environmental sound. This implementation, including technical documentation, code, and sound library with strong labelling, is presented under an open-source license to encourage future collaborative research. Finally, the paper offers suggestions on further developing the apparatus to reach a systematic and near real-time soundscape analysis with the development of a machine learning system.

The Political and Economic Dependence of the Press in Macao under Portuguese and Chinese Rule: Continuity and Change - Costa-Ribeiro, Nelson; Simões, José Manuel (Communication & Society, 2021)
The article analyses the media system in Macao, a special administrative region of China that transitioned from Portuguese to Chinese sovereignty in 1999, becoming one of cities in the world with the largest number of published newspapers per capita. Combining historical research with the analysis of contemporary empirical data collected through interviews with journalists working on the ground, the research demonstrates how there is a long tradition of state control that goes back to the colonial era and that has assumed different forms, ranging from outright censorship to physical intimidation of journalists and economic dependence on the government. Limitations and control strategies imposed on news reporting during the Portuguese administration continue to be practiced today by the Chinese authorities. Even so, journalists operating on the Macao media market tend to overstate the level of freedom they are given, which can be attributed to media outlets being economically dependent on the state. Nevertheless, the level of freedom attributed to the press is today higher than it had been during the colonial period with some critical voices being allowed to reach the media. This needs to be understood in the context of what has been defined as the Chinese safety valve strategy.
Keywords: Censorship; Journalism Practice; Media Systems; Press Freedom; Press Subsidies